Pemodelan 2D Daerah Rawan Banjir Sungai Lepo – Lepo Kota Kendari - Ilham, Vickky Anggara; Makkawaru, Andi; Sudardjat, Catrin; Rahmadhani Asana, Annur (Sultra Civil Engineering Journal (SCiEJ), 2024)
Research was carried out to see the potential for flooding through Computational Fluid Dynamic simulations, namely a set of methodologies that allow computers to provide numerical simulations of fluid flow. The entire system is transformed into virtual form, and can be visualized via computer. Components in fluid dynamic computing include selection of mathematical models, discretization, numerical analysis schemes, numerical solutions and representation of processes numerically and graphically. Flood mapping can provide information about which areas need special attention so that it can be used as a reference in making policies related to flood management and can be used to increase wider public awareness regarding floods. The HEC-RAS permanent flow module is able to take into account the influence of various flow obstacles, such as bridges, culverts, bends, or obstacles on riverbanks. The permanent flow module is designed for use in riverbank management environments and the determination of flood risk insurance regarding the determination of riverbanks and floodplains. The permanent flow module can also be used to estimate changes in water level due to channel improvements or embankment construction. HEC-RAS permanent flow special module features include double plan analysis, double profile calculation, double culvert or gate analysis, flow optimization, and stable channel design and analysis. From the simulation results and depth classification, information on the area of inundation and areas prone to flood inundation on the Lepo-Lepo River is 29.34 Ha.